A New Procedure for Simulating Active Lateral Force in Spatially Variable Clay Modeled by Anisotropic Random Field. (11th August 2015) - Hu, Y.-G.; Ching, J.
Abstract : A new procedure for simulating the active lateral force (Pa ) is proposed for clays with anisotropic spatially variable undrained shear strength (su ). With the proposed procedure, the Pa samples can be simulated without the use of the random field finite element method ( RFEM ). It requires only simple algebraic calculations and chart checking. Two retaining wall examples with isotropic or anisotropic random field are used to demonstrate the effectiveness of the proposed procedure.